Pengaruh Kadar Perekat Papan Komposit Tandan Kosong Kelapa Sawit pada Taraf Intensitas Bunyi - Fatisa, Huril; Nugroho, Bintoro Siswo; Nurhanisa, Mega; Wahyuni, Dwiria; Asri, Asifa (Universitas PGRI Sumatera Barat, 2023)
A study was performed to analyze the sound intensity level and physical properties of a composite board made from oil palm empty fruit bunch (OPEFB) particles mixed with polyvinyl acetate (PVAc) adhesive. The composite boards were fabricated with various concentrations of adhesive, namely 8%, 10%, 12%, 14%, and 16%. The intensity level was measured at sound wave frequencies of 125 Hz, 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, and 4000 Hz. The results showed that the highest sound intensity level, 74,2 dB at a frequency of 500 Hz, was found in the composite board with an 8% adhesive concentration. This composite board is categorized as a low-density composite board. The lowest sound intensity level, 58,6 dB at a frequency of 125 Hz, was found in the composite board produced with 16% adhesive concentration. This composite board is categorized as a high-density composite board. The physical property test results for all adhesive concentration variations showed that the resulting composite board density was 0,705-0,723 g/cm3, and the moisture content was 8,36%-9,66%. These values met the requirements of SNI 03-2105-2006. Keywords : Composite Boards, Sound Intensity Level, Composite Physical Properties